2003
DOI: 10.1001/archsurg.138.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Sentinel Lymph Node Biopsy in Patients With Pure Ductal Carcinoma In Situ of the Breast

Abstract: Hypothesis: A sentinel lymph node (SLN) biopsy should not be considered a standard procedure in the treatment of all patients with ductal carcinoma in situ (DCIS) of the breast if the lesion is completely excised by radical surgery and there are free margins of resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
2
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 16 publications
3
63
2
7
Order By: Relevance
“…They found that sentinel lymph nodes were positive for disease in 10% of patients with microinvasive DCIS (n ϭ 31) and in 12% of patients with palpable masses, masses evident on mammograms, or extensive high-grade lesions (n ϭ 76). In a European Institute of Oncology study of 223 unselected consecutive patients with pure DCIS, sentinel lymph node biopsy found nodal metastasis, mostly micrometastasis, in 3.1% of patients (n ϭ 7) [41]. More recently, Yen and colleagues evaluated 398 patients with an initial diagnosis of DCIS [42].…”
Section: Surgery For Dcismentioning
confidence: 99%
“…They found that sentinel lymph nodes were positive for disease in 10% of patients with microinvasive DCIS (n ϭ 31) and in 12% of patients with palpable masses, masses evident on mammograms, or extensive high-grade lesions (n ϭ 76). In a European Institute of Oncology study of 223 unselected consecutive patients with pure DCIS, sentinel lymph node biopsy found nodal metastasis, mostly micrometastasis, in 3.1% of patients (n ϭ 7) [41]. More recently, Yen and colleagues evaluated 398 patients with an initial diagnosis of DCIS [42].…”
Section: Surgery For Dcismentioning
confidence: 99%
“…However, this is still controversial in DIN patients. In fact, for some authors SLNB should not, in general, be indicated [62]; for others, SLNB should always be carried out [63][64], and for others still, it should be performed only in certain specific and particular cases [65][66][67][68]. Major cancer centers agree that SLNB should be conducted a)…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…A study by Intra et al showed that examination of SLN by serial sectioning and IHC increases the detection rate of metastasis from, 9-33% in infiltrating carcinoma 27 .…”
Section: Sentinel Lymph Node Biopsy Techniquementioning
confidence: 99%